The noun phrase structure in Nigerian English - Lamidi, Mufutau T. (Adam Mickiewicz University, 2007)
Scholars have described Nigerian English in different ways. While some see it as a language that is evolving from a bilingual/multilingual background with influences from multiple languages, some see it as a deviation from the norm (and therefore a body of institutionalised errors): the former, from the perspective of a foreign or L2 speaker; the latter, from the perspective of a native speaker. Nevertheless the arguments for the existence of Nigerian English are quite convincing. It is therefore necessary to codify the grammar of the evolving language. Based on the data generated from newspapers, scholarly works in English and speeches recorded from the broadcast media, this study explains the grammatical/syntactic structure of the Noun Phrase in Nigerian English. Using a simple descriptive method, this paper discusses the Noun Phrase structure of Nigerian English from the perspective of accommodation rather than deviation. This idea (of accommodation) makes it possible to adduce reasons for the occurrence of specific structures and identify errors which are not products of language contact.